Influence of the pH of li-rich Li1.2Mn0.54Ni0.13Co0.13O2 on the electrochemical performance by sol–gel method. Issue 200 (24th July 2019) - Song, Changkun; Feng, Wangjun; Su, Wenxiao; Chen, Linjing; Li, Miaomiao
Abstract: The positive electrode material of the lithium-rich layered oxide has poor capability, and its cycle stability and rate characterizations have not been satisfactory. The lithium-rich cathode material Li1.2 Mn0.54 Ni0.13 Co0.13 O2 with different particle sizes was obtained by adjusting the pH by sol–gel method. The results show that the electrochemical performance of the material is optimal at pH = 9.0. It initial discharge capacity of 262.5 mAh/g at 0.1 C between 2.0 and 4.8 V. The high reversible discharge capacities is still of 161.0 and 133.7 mAh/g after 100 cycles at 0.5 C and 2 C, with a high capacity retention of 80.46% and 84.14%, respectively. This excellent electrochemical performance is attributed to smaller and uniform particles